Study of Living Hadith Toward The Practice of Fasting Mondays and Thursdays at the Maqamam Mahmuda Islamic Boarding School Central Aceh - Jannah Lukman (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
It is believed that Monday-Thursday Sunnah fasting can improve the spiritual quality of the students who practice it. Then how is this practice that comes from the Hadith successfully practiced by the students? What is the effect on the character and spiritual building of santri? This study describes the practice of Monday Thursday fasting; teaching method of the Hadith fasting Monday Thursday; and the attention from the Islamic boarding school in reviving the Monday-Thursday fasting in Islamic boarding school environment. The study was conducted in the Maqamam Mahmuda Islamic Boarding School, Central Aceh by using qualitative methods for collecting the data. While the data obtained were analyzed by deductive and inductive methods. After being researched, the the Islamic boarding school has carried out this sunnah of fasting activity very well. This practice of fasting was carried out for the good response of the students to the Hadits of Monday-Thursday fasting Hadith that was taught. In fact, the students do it on their own consciousness. This also has affected the spirituality of the santri, namely the spirit of doing good deeds; exercise patience; educating morality and controlling desire.